2014
DOI: 10.1089/jpm.2013.0227
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Palliative Care Team on Residents' Experiences and Comfort Levels with Pediatric Palliative Care

Abstract: Reported presence of a PCT may be associated with greater resident comfort in providing PPC and a more accurate understanding of PPC. There remains ample opportunity to educate pediatric and IM/Peds residents in PPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 31 publications
(45 reference statements)
0
13
0
Order By: Relevance
“…; Wu et al. ). Therefore, hospitals might consider rotating nurses through hospice units as an institutional strategy to provide training in end‐of‐life care.…”
Section: Discussionmentioning
confidence: 98%
“…; Wu et al. ). Therefore, hospitals might consider rotating nurses through hospice units as an institutional strategy to provide training in end‐of‐life care.…”
Section: Discussionmentioning
confidence: 98%
“…Despite a growing recognition that bereavement care is inherent to good clinical care, physicians often receive little training on how to compassionately and professionally communicate with families after a loss. 14,15,18,21,29,30 Many physicians learn about bereavement care from mentors or through a ''trial and error'' approach rather than through dedicated training. 18 Most pediatric oncology fellows do not receive specific education in provision of bereavement care as this is not part of the required curriculum.…”
Section: Discussionmentioning
confidence: 99%
“…Both self-care and communication interventions may also help minimize burnout, which is known to diminish compassionate care and is unfortunately common in both pediatric and oncology physicians. [28][29][30][31][32][33] This study offers insight into the bereavement practices of pediatric oncologists, a subspecialty with clinically relevant perspectives regarding the care of children with life-limiting conditions. There are relevant limitations recognized by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…Curricular models have recently been developed for palliative care competencies in medical school and residency programs [1,2]. Formal palliative care teaching positively impacts medical residents’ knowledge and comfort level with palliative care [3]. A prior study exploring six hours of palliative care education revealed statistically significant improvement in pediatric resident learning and confidence after curricular implementation [4].…”
Section: Introductionmentioning
confidence: 99%